Optimal Recloser Placement in Rural and Urban 11 kV Distribution Feeders of Nepal Based on Reliability and Cost–Benefit Analysis - Gurung, Chij Bahadur; Gautam, Basanta Kumar; Ray, Sochindra Kumar (Journal of Advanced College of Engineering and Management, 2026)
Reliability improvement of distribution systems is a major concern for utilities in Nepal due to frequent interruptions in both rural and urban feeders. This study investigates the optimal placement of auto-reclosers in two practical 11 kV feeders: Feeder-4 (urban) under the Birgunj Distribution Center and the Khoplang feeder (rural) under the Gorkha Distribution Center. Base-case reliability indices (SAIFI, SAIDI, CAIDI, and EENS) were evaluated using analytical modeling and ETAP simulation. A Genetic Algorithm (GA)-based optimization framework was developed to minimize Expected Energy Not Supplied (EENS) and maximize economic benefits. The results indicate that 2 reclosers are optimal for the Feeder-4 (urban) feeder and 4 recloser for the Khoplang (rural) feeder. SAIDI and EENS were reduced by more than 55% in both feeders. Cost–benefit analysis yielded benefit–cost ratios greater than 2.0 and payback periods of less than four years, confirming economic feasibility.